Palmitic acid ester of tetrahydrocannabinol (THC) and palmitic acid diester of 11-hydroxy-THC — Unsuccessful search for additional THC metabolites in human body fluids and tissues. (January 2019) - Kraemer, Michael; Broecker, Sebastian; Diehl, Bernd W.K.; Madea, Burkhard; Hess, Cornelius
Highlights: Syntheses of palmitic acid esters of THC (monoester) and 11-hydroxy-THC (diester). Structural elucidation of synthesis products by means of NMR and LC–QToF–MS. Analysis of esters in human body fluids/tissues by LC–QQQ–MS. Cannabinoid palmitic acid esters could not be detected in human samples. Abstract: Fatty acid conjugates of hydroxy-metabolites of tetrahydrocannabinol (THC) or cannabinol have already been reported as metabolites in rats. In the herein presented investigation, palmitic acid esters of THC and its primary metabolite 11-hydroxy-delta9-tetrahydrocannabinol (11-OH-THC) were synthesized using esterification with palmitic acid chloride. Structural elucidation of the products was conducted using nuclear magnetic resonance spectroscopy (NMR) and liquid chromatography coupled to quadrupole time of flight mass spectrometry (LC–QToF–MS). For the confirmation of a previous cannabis use, body fluids (femoral blood, heart blood, urine, bile) of 27 death cases (all with known cannabis use), including adipose tissue homogenates of six of these cases as well as eleven plasma samples (probably all with regular cannabis use, confirmed by a high 11-nor-9-carboxy-delta9-tetrahydrocannabinol (THC-COOH) concentration (except one sample, >200 ng/mL), were tested for THC and its main metabolites 11-OH-THC and THC-COOH using gas chromatography coupled to mass spectrometry (GC–MS). These samples as well as further tissue homogenates of autopsy cases (liver, kidney, brain) were additionally tested for the presence of THC palmitic acid ester or 11-OH-THC palmitic acid diester by means of a liquid chromatographic triple quadrupole mass spectrometric (LC–QQQ–MS) method, in order to evaluate a possible presence of these conjugates in humans. In none of the analyzed samples (in total 196 specimens; plasma (N = 11), femoral blood (N = 23), heart blood (N = 25), urine (N = 23), bile (N = 27), liver (N = 27), kidney (N = 27), brain (N = 27), adipose tissue (N = 6)), palmitic acid esters of THC or 11-OH-THC could be proven. Even if the existence of these esters in human samples cannot be ruled out definitely, suitability as cannabis consumption markers does not seem likely based on our findings.